2015
DOI: 10.4238/2015.june.18.17
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between zinc finger protein 36 (ZFP36) gene polymorphisms and obstructive sleep apnea

Abstract: ABSTRACT. Recent data have indicated that inflammation may have an important correlation with obstructive sleep apnea (OSA). Studies have indicated a relationship between OSA and TNF-α gene polymorphisms. Zinc finger protein 36 (ZFP36) regulates TNF-α mRNAs. However, ZFP36 gene polymorphisms have not been investigated in OSA. Therefore, we conducted the present case-control study to assess whether variances in ZFP36 gene polymorphisms account for differences in TNF-α levels in patients with moderate-tosevere O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…In addition, two crucial ferroptosis genes, CD44 and ZFP36, experimentally validated, exhibited a positive correlation with macrophages, with CD44 showing a particularly strong association. ZFP36, namely zinc finger protein 36, exerts an influence on the stability of TNF-α mRNA and a recent study has revealed that the disruption of ZFP36 in mice led to the development of a multifaceted inflammatory syndrome due to elevated TNF-α production [42] and further attracts macrophage infiltration. In this study, we first revealed ZFP36 protein expression were downregulated in DKD kidney tissues and in podocyte MPC5 and mesangial SV40-MES-13 cells after HG stimulation,while the downregulation of ZFP36 can trigger the activation of ferritinophagy and the initiation of ferroptosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two crucial ferroptosis genes, CD44 and ZFP36, experimentally validated, exhibited a positive correlation with macrophages, with CD44 showing a particularly strong association. ZFP36, namely zinc finger protein 36, exerts an influence on the stability of TNF-α mRNA and a recent study has revealed that the disruption of ZFP36 in mice led to the development of a multifaceted inflammatory syndrome due to elevated TNF-α production [42] and further attracts macrophage infiltration. In this study, we first revealed ZFP36 protein expression were downregulated in DKD kidney tissues and in podocyte MPC5 and mesangial SV40-MES-13 cells after HG stimulation,while the downregulation of ZFP36 can trigger the activation of ferritinophagy and the initiation of ferroptosis [43].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, ZFP36 obtained from model screening is a zinc finger protein affecting TNF- α mRNA's stability. Zhang et al found that the inactivation of ZFP36 in mice resulted in a complex inflammatory syndrome caused by increased TNF- α production [ 35 ]. Some studies have reported that the level of ZFP36 in diabetic patients was significantly lower than in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data have indicated that inflammation may play an important role in OSA ( 44 ). Zhang et al found that the genotype distribution of single nucleotide polymorphisms rs251864 and rs17879933 in ZFP36 were significantly different between moderate-to-severe OSA patients and control controls, but they were not directly associated with sleep apnea parameters, suggesting that ATF may be involved in regulating OSA in cooperation with other factors ( 45 ). It has also been reported that overnight IH in patients with OSA induces expression of DUSP1 , which may mediate increases in manganese superoxide dismutase (MnSOD) expression and activity, contributing significantly to neutralizing the effects of the ROS elicited by OSA ( 46 ).…”
Section: Discussionmentioning
confidence: 99%